EFFICIENCY OF METAL SCRAP SEPARATION IN EDDY CURRENT SEPARATOR - Gordan Bedeković; Branko Salopek; Ivan Sobota (Rudarsko-geološko-naftni Zbornik, 2008)
Eddy-current separation is most often method used for the recovery of non-ferrous metals (Al, Cu, Zn, Pb) from solid wastes and also for separating non-ferrous metals from each other. The feed material comes to rotary drum and magnetic field by belt conveyer. The changing magnetic field induce eddy currents in conductive (metallic) particles. Because interaction between this currents and the magnetic field electrodynamic forces will act on conductive particles. Therefore the trajectories of conductive particles will be different from the trajectories of the non-conductive ones. Separation is a result of the combined actions of several forces (electrodynamic, gravitational and frictional). The paper presents results of aluminium recovery from mixture of metallic particles in eddy current separator. Testing were conducted under field condition. Results shows that is possible achieve recovery of 99 % and concentrate quality of 89 % of aluminium (the paper is published in Croatian).